2016
DOI: 10.1039/c5cc08163g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of geminal bis- and tristriazoles: exploration of unconventional azide chemistry

Abstract: A range of geminal bis- and tristriazoles are presented. These rare and hardly studied compound classes were easily synthesized using ethyl 2,2-diazido-3-oxobutanoate as the common starting point. Firstly, CuAAC-reaction with an alkyne afforded the corresponding deacetylated bistriazoles. Upon further azidation yielding azidomethylenebistriazoles, a second CuAAC-functionalization then led to the creation of the geminal tristriazole compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 50 publications
(3 reference statements)
0
16
0
Order By: Relevance
“…Our previous studies with 2,2‐diazido carbonyl systems have demonstrated how the neighboring diazido group is capable to ease the amine addition, and thus the carbonyl group may be considered as being highly activated in those systems. [10f], [11a], , From a mechanistic point of view, we assume that the present fragmentation starts with the nucleophilic attack of the amine onto the carbonyl group of diazide A , as outlined in Scheme . Upon addition‐elimination, a diazido leaving group B (or its deprotonated form) may be generated that undergoes further degradation through loss of both dinitrogen and an azide anion under basic conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies with 2,2‐diazido carbonyl systems have demonstrated how the neighboring diazido group is capable to ease the amine addition, and thus the carbonyl group may be considered as being highly activated in those systems. [10f], [11a], , From a mechanistic point of view, we assume that the present fragmentation starts with the nucleophilic attack of the amine onto the carbonyl group of diazide A , as outlined in Scheme . Upon addition‐elimination, a diazido leaving group B (or its deprotonated form) may be generated that undergoes further degradation through loss of both dinitrogen and an azide anion under basic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…This experimental procedure allows for the straightforward installation of diazide units with 1,3‐diketones and, more importantly, 3‐oxo esters. In a number of subsequent studies regarding the reactivity of diazidated compounds 2 , we revealed that treatment with primary amines typically leads to a rapid fragmentation of the carbon core: The diazides are excellent acylation reagents, and amides 3 are easily formed besides a hazardous diazidated leaving group 4 …”
Section: Introductionmentioning
confidence: 99%
“…As depicted in Scheme 10, ethyl 2,2‐diazido‐3‐oxobutanoate 29 resulted in the formation of bistriazole 30 , which was then converted into the quite unique tristriazole 32 through a two‐step azidation‐cycloaddition sequence. [ 47 ]…”
Section: Reactivities Of Geminal Diazidesmentioning
confidence: 99%
“…azoles 30 attached to a tertiary carbon center. 17 By employing ethyl 2,2-diazido-3-oxobutanoate (29) as the starting compound, the double cycloaddition was directly followed by the smooth cleavage of the acetyl group under aqueous conditions. The method allows for the incorporation of geminal bistriazoles containing aryl systems, alkyl groups, and electron-withdrawing carbonyls with yields ranging from 19% to 91%.…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…Kirsch et al approached this problem in a twostep synthesis starting from bistriazole 30 (Scheme 28). 17 Oxidative replacement of the ethyl ester provides the corresponding azidomethylenebistriazole 102; a subsequent CuAAC reaction then results in the formation of the gemi-nal tristriazoles 103. IBX-SO 3 K, was crucial for the decarboxylative azidation reaction and found previous applications for the synthesis of, for example, geminal triazides 53 and diazides (intermediates for the synthesis of geminal bistriazoles, Scheme 4).…”
Section: Scheme 27 Synthesis Of Geminal Trisbenzotriazole 101mentioning
confidence: 99%